A study of how the utilisation of optimal cost management techniques influence medical scheme administrators - Seugnet Bronkhorst; Leon Dan Schmidt (The journal of accounting and management, 2017)
Within todays competitive and cost-driven business environment, Medical Scheme Administrators are under tremendous pressure to ensure their operations are at the pinnacle of financial performance, through stable but profitable business structures, whilst achieving maximum return for members contributions. The purpose of the study was to identify the factors that affect the optimal cost management practices is to ensure that organisations have a true understanding of costs, so that it can continuously make the right decisions with regards to product mix, price and market. This research uses a qualitative methodology to uncover how the South African Medical Scheme Administrators currently use costing principles. This is achieved through semi-structured interviews with individuals, who are directly responsible for this function within their respective organisation. The study concluded that a conceptual cost management framework, which is made up of a number of key models to assist an organisation, is more frequently used in more mature organisations. Purpose: The purpose of the study is to assess how active, mature and prevalent, cost management featured within South Africas Medical Scheme Administrators. Problem Investigated: A great amount of literature exists on the subject of cost containment and effectiveness of system employed in MSA environment. There is however, no conclusive evidence on the utilisation of optimal costing models and the techniques of how quality of care is affected by cost containment strategies is obtainable. MSA has changed the face of private healthcare in South Africa, but so little is known about its impact on cost and cost management technique employed. Therefore the problem statement is to identify that the MSA are achieving effective cost management performance through the utilisation of optimal cost management techniques. Methodology: Due to both the economic and social implications faced by the Medical Scheme Administrators (MSA) regarding the cost techniques utilised, the research approach of the study was of a qualitative research. This approach was exploratory in nature with the core focus of the research the cost management techniques employed by MSA to achieve optimal cost management. A structured interview based research methodology was substantiated. The populations for this study were the MSA who are registered with the Council for Medical Schemes and are operational in South Africa, covering both open and closed medical schemes in South Africa. The population were all senior employees employed responsible for the cost management function of MSA in the South Africa environment. The population is a heterogeneous population. The sample size of the study were the number of the respondents that the researcher was able to interview within the set time frame/period, whilst ensuring sufficient coverage/ population representation is achieved.
2668125-0; 2392-8778; The journal of accounting and management; 718053745